ANALISIS PENINGKATAN PRODUKTIVITAS KARYAWAN PT. ASIA RECYCLE MANDIRI DITENGAH DAMPAK COVID-19 ANALYSIS OF EMPLOYEE PRODUCTIVITY IMPROMENT OF PT. ASIA RECYCLE MANDIRI IN THE IMPACT OF COVID-19 - Citra Perdana, Dian Noor (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2023)
ABSTRACT The purpose and adama of this research is to find out more about Kaia Eink Environment, Lanzhement Kenia Nern Eink,And The Discipline of the Body Karancan Productivity PT. Asia Recycle Mandiri This research includes descriptive research. The research methodology uses a quantitative approach, in the questionnaire. A sample of 75 respondents from 270 population. then the questionnaires were distributed to PT. Asia Recycle Mandiri The data used concumes primary data in the form of a questionnaire, which has been prepared by respondents from the secondary data sector and you are an internet librarian. The analytical method used is quantitative analysis of validity and reliability, multiple linear tegeu shows that there is a positive influence of physical work environment and creative discipline on the deactivation of the test carpet (parallel test) and the ketia Eisik environment, the tcount value of 2.341 > 1.996 with a significant value of 0.022 < 0,05. The test results from the Non Physical Third Environment have an anzatif and insignificant direction with a tcount value of -0.450 table 1.996 and a significant value of 0.654 > 0.50. Meanwhile, test baul and word discipline have tcount of (6.791) < ttable (1.996) and unificans value of 0.000 < 0.05